Recessão e desempenho das firmas: uma abordagem multinível de curva de crescimento - Goldszmidt, Rafael Guilherme Burstein (2010)
This thesis was aimed at studying the determinants of the impact of recessions on the performance of firms. More specifically, it addressed the U.S. recession of 2001. The sample of companies analyzed, taken from Compustat, included annual data between the years 1998 and 2004 from 510 firms operating in 55 different manufacturing industries. Performance was operationalized by three different accounting indicators. A multilevel growth curve model allowed the analysis of the impact of the crisis on company performance. The decomposition of the variability of the recession impact on performance indicated that firm effects are predominant, ie, the variation in performance during the crisis is largely determined by idiosyncratic characteristics of firms and not by attributes of the sectors in which they operate. However, industry effects were more important during a recession than during times of economic growth. The findings concerning the correlation between the impact of the crisis and the past performance of companies indicated that a recession does not amplify performance differences between firms extant before the crisis, but changes their performance relative position. These results suggest that the characteristics of firms which provide competitive advantage in times of economic growth do not necessarily make them less susceptible to the effects of a recession. Available organizational slack, which has as one of its main components cash reserves, was examined as an explanatory variable of the recession's impact on performance at the firm level. The hypothesis of an inverted 'U' relationship was tested and not confirmed. A significant negative linear relationship was found, ie companies with high cash levels suffered the most during the recession. These results are justified, theoretically, by managerial complacency caused by excess slack which may lead executives not to adapt to a new economic context, but to use available liquid assets to “pay the price” of the firm's lack of fit to its external environment. This finding proved to be robust in the three different operationalizations of performance and in two measures of available organizational slack. Company growth during the recession was also 8 controlled for, so that this result does not just represent a trade-off between growth and profitability; ie, it is not derived from a company's decision of using the crisis as an opportunity to expand its market share at the expense of shortterm profitability. The managerial implications of these findings suggest that economic crises deserve special attention and that good performance in times of stability does not ensure success during a recession. The mere stockpiling of cash does not appear to be an appropriate preventive measure and the tendency by firms of accumulating reserves of liquid assets as a precaution against macroeconomic fluctuations should be taken with caution. Despite the breadth of the study, the sample used included only manufacturing firms which remained active between 1998 and 2000, reducing the range of application of the results obtained.